Global transmission of monkeypox virus—a potential threat under the COVID-19 pandemic - Wang, Yang; Leng, Ping; Zhou, Hao (Frontiers in Immunology, 2023)
Monkeypox virus (MPXV) cases have increased dramatically worldwide since May 2022. The Atlanta Center for Disease Control and Prevention (Atlanta CDC) had reported a total of 85,922 cases as of February 20th, 2023. During the COVID-19 pandemic, MPXV has emerged as a potential public threat. MPXV transmission and prevalence must be closely monitored. In this comprehensive review, we explained the basic characteristics and transmission routes of MPXV, individuals susceptible to it, as well as highlight the impact of the behavior of men who have sex with men (MSM) and airline traveling on recent outbreaks of MPXV. We also describe the clinical implications, the prevention of MPXV, and clinical measures of viral detection.